Polska pieśń na Litwie na tle sytuacji socjolingwistycznej i etnokulturowej - Krupowies, Maria (Kalbotyra, 1997)
The article deals with the Polish musical repertoire of Polish spoken regions of Lithuania and the conditions of its function in the complicated multiethnic and multicultural situation of East Lithuania. The results of investigation shows that: 1) Polish musical repertoire in Lithuania presents a local variant of the popular repertoire spread throughout Poland and its borders in the ninteenth - twentieth c.; 2) Polish musical repertoire in Lithuania is spread over borders of the current Polish population while Polish folk songs are sung by Lithuanians and Belarussians from the neighbouring regions as well; 3) The Polish folk songs in Lithuania present the product of cultural marginality: it contains manifestations of Lithuanian and Belarussian substrata; 4) the structure of musical repertory and musical preferences of the Polish population in Lithuania are determined by their national consciousness and sociolinguistic situation (on the level - nobles - peasants).